A SOCIOLINGUSTICS AND YOUNG LEARNERS SOCIOLINGUISTIC FACTORS AFFECTING YOUNG LEARNERS IN LEARNING ENGLISH LANGUAGE AS A FOREIGN LANGUAGE - Usein, Arafat (International Scientific Journal Vision, 2017)
Young Learners in general can be defined as learners in Primary School aging 9-10 years old who are learning English as a Foreign Language. Sociolinguistics is the study of a language to social factors including differences of regional, class and occupational dialect, gender differenced and bilingualism. In this study the relation between language and society will be analyzed and discussed - a branch of both linguistics and sociology. Furthermore, we will specify how the Young Learners learn the English Language using the most effective skills of children’s productive use-reading and writing in relation to Sociolinguistics and what are their optimum age of learning, their categories, the advantages of early acquisition of the Second language. A research was applied to check at what size the group of Young Learners’ handwriting have improved and in the following, the Social Background Questionnaire was administered to check out at what extend their social background affect to the improvement of their writing. The children have their own characteristics and they are different from adults. They cover their way of thinking, their aptitude. To give the best quality the teachers should know to understand them well.